2010
DOI: 10.3183/npprj-2010-25-02-p156-161
|View full text |Cite
|
Sign up to set email alerts
|

Review: Reduction of energy consumption in TMP refining through mechanical pre-treatment of wood chips

Abstract: SUMMARY:This review covers the effect of mechanical pre-treatment of wood chips on the energy consumption in refining and the quality of pulp. To understand the mechanisms of mechanical pre-treatment, a short description of relevant refining theory and reported effects of pre-treatment on wood morphology is given. Mechanical pre-treatment offers a chance to utilize the energy needed to defibrate chips in a more efficient way, minimizing the cyclic elastic deformations which are the main defibration mechanism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 2 publications
0
25
0
1
Order By: Relevance
“…In addition, energy demand can be decreased by reducing raw materials variability (Dundar et al 2009 ) or by changing the spout angle of wood chipper (Hellstr ö m et al 2011 ). In TMP production, however, other factors have been shown to decrease the energy demand, such as decreasing discharge consistency from the primary refiner, on a double-stage refiner (Alami et al 1997 ), increasing refining temperature/pressure (Muh í c et al 2010 ), and compressing chips before refining (Gorski et al 2010 shown to affect TMP process energy demand (Lanouette et al 2010 ). The studies regarding the understanding of the main variables affecting the refining energy demand, such as the chemical and morphologic structure of wood, are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, energy demand can be decreased by reducing raw materials variability (Dundar et al 2009 ) or by changing the spout angle of wood chipper (Hellstr ö m et al 2011 ). In TMP production, however, other factors have been shown to decrease the energy demand, such as decreasing discharge consistency from the primary refiner, on a double-stage refiner (Alami et al 1997 ), increasing refining temperature/pressure (Muh í c et al 2010 ), and compressing chips before refining (Gorski et al 2010 shown to affect TMP process energy demand (Lanouette et al 2010 ). The studies regarding the understanding of the main variables affecting the refining energy demand, such as the chemical and morphologic structure of wood, are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some low energy refining experiments have been based on process optimization (Senger et al 2006;Muhic et al 2010;Murton and Duffy 2005) and the aid of chemicals in sulphonation, carboxylation, oxidation, and enzymatic reactions (Johansson et al 2011;Kumar and Wyman 2009;Decker et al 2009). In those studies that involved refining, the focus was mainly on the refining equipment (Gorski et al 2010;Kure et al 1999), and there was less discussion on adjusting fiber morphology to reduce refining energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…In the Nordic countries, a larger share of paper production uses mechanical pulp than anywhere else in the world (Ruohonen, Ahtila 2011). Energy-efficient refining has been an important research subject for a long period of time (Engstrand et al 2003;Engstrand et al 1989;Gorski et al 2010;Höglund et al 1994;Muhic et al 2010;Norgren, Höglund 2009;Sabourin 1999). The institute of Fibre Science and Communication Network (FSCN) at Mid Sweden University, together with Scandinavian forest and supplier companies, the Pulp and Paper Research Institute (PFI), and other Scandinavian universities, is working with a large research program with the goal of showing how to design the TMP and CTMP mills of the future.…”
mentioning
confidence: 99%